EVALUATION OF MANAGEMENT IN IMPROVING THE QUALITY OF AQIDAH AKHLAK LEARNING - Nur Adianah (UNISAN JURNAL, 2024)
The Sekolah development plan generally includes the formulation of the madrasa's vision, mission, objectives and implementation strategies. While the Sekolah annual work plan generally includes the identification of Sekolah targets (madrasaal situational objectives), selection of madrasa functions needed to achieve the identified targets, SWOT analysis, problem-solving steps, and preparation of plans and annual work programs for madrasas. This type of research is an evaluation research using qualitative research methods. According to Sugiyono, evaluation research is research that aims to compare an event, activity and product with predetermined standards and programs, so that evaluation research serves to explain the phenomenon. Aqidah Akhlak at SMA N 4 Bandar Lampung. The results of the study stated that at the planning stage it was quite good. In general, the implementation of madrasa-based management in improving the quality of Aqidah Akhlak learning at SMA N 4 Bandar Lampung includes: Management of curriculum and teaching programs, management of education personnel, student management, financial management, management of facilities and infrastructure and management of madrasa relations with the community. Basically, the implementation of madrasa-based management in various fields has been going well. The supporting factors for the implementation of madrasa-based management in improving the quality of learning aqidah morality at Mts Al-Hikmah Merau include: experienced madrasa principals, teacher academic qualifications in accordance with the subjects being taught, and teachers already have professional abilities.